2015
DOI: 10.1186/s12871-015-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnesium sulphate on bi-spectral index (BIS) values during general anesthesia in children

Abstract: BackgroundMagnesium was reported to reduce both the anesthetic requirements and the period needed to reach a bi-spectral index value of 60 when used intra-operatively (Br J Anaesth 83:302-20, 1999; Anesth Analg 20:1273-5, 1988; Br J Anaesth 89:594-8, 2002; Anesth Analg 87:206-10, 1998; Br J Anaesth 89:594-8, 2002; Br J Anaesth 94:438-41, 2005) and to minimize the emergence agitation (Anaesthesia 61:1058-63, 2006). Previous studies examined the influence of magnesium on the anesthetic requirements while the bi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…With regard to neuropathic pain, a recent randomized, placebo controlled, double blind, crossover trial evaluated the use of 1.5% topical diclofenac for neuropathic pain from PHN and complex regional pain syndrome. The authors found that after 2 weeks of topical application, subjects who received diclofenac had less pain compared to placebo on the visual analogue scale (VAS) ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to neuropathic pain, a recent randomized, placebo controlled, double blind, crossover trial evaluated the use of 1.5% topical diclofenac for neuropathic pain from PHN and complex regional pain syndrome. The authors found that after 2 weeks of topical application, subjects who received diclofenac had less pain compared to placebo on the visual analogue scale (VAS) ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…MgSO 4 (20–50 mg·kg −1 ± 5–20 mg·kg −1 ·h −1 ) reduces the need for sedative‐hypnotic drugs during general anesthesia: it can decrease the sevoflurane minimum alveolar concentration by 50% and the induction dose of propofol; it shortens the latency time until a bispectral index value <60 is reached; and it reduces ventilation requirements (tidal volume and respiratory rate) as metabolism decreases (O 2 consumption and CO 2 production) .…”
Section: Magnesium Sulfate In Pediatric Anesthesiamentioning
confidence: 99%
“…Tracheal intubation (IV) (31) 30 mgÁkg À1 Laryngospasm (IV) (23,33,34) 15 mgÁkg À1 Bronchospasm (IV) (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) 50-100 mgÁkg À1 + 40-50 mgÁkg À1 Áh À1 Bronchospasm (nebulized) (47)(48)(49)(50)(51)(52)(53)(54)(55) 40 mgÁkg À1 or 150 mg (total dose) Antiadrenergic response Cardiopulmonary bypass (IV) (57-60) 25-50 mgÁkg À1 Long QT syndrome (IV) (61) 30-50 mgÁkg À1 + 5-20 mgÁkg À1 Áh À1 Neonatal pulmonary hypertension (IV) (63) 200 mgÁkg À1 + 20-150 mgÁkg À1 Áh À1 Pheocromocytoma (IV) (64) 30-50 mgÁkg À1 + 5-20 mgÁkg À1 Áh À1 Organ protection Neuroprotection (IV) (68-72) 250 mgÁkg À1 Áday À1 Myocardial protection (cardioplegia) (73,74) 40-80 mgÁkg À1 Hypomagnesemia Perioperative hypomagnesemia (IV) (58,59) 25-50 mgÁkg À1 AE 5-20 mgÁkg À1 Áh À1 alveolar concentration by 50% and the induction dose of propofol; it shortens the latency time until a bispectral index value <60 is reached; and it reduces ventilation requirements (tidal volume and respiratory rate) as metabolism decreases (O 2 consumption and CO 2 production) (2,6). Sevoflurane has certain excitatory effects on the central nervous system, which may be associated with increased seizure activity in children.…”
Section: Muscle Relaxationmentioning
confidence: 99%
“… 2 , 3 Additionally, the element has potential analgesic and sedative properties; therefore, it is useful as an adjuvant during general anesthesia. 4 Previous study 5 have examined the effects of magnesium on anesthetic agent doses needed to keep bispectral index (BIS) values within fixed ranges. However, only a single pediatric study 5 has evaluated the effect of intraoperative magnesium on BIS values while operation type and end-tidal anesthetic concentration were kept constant.…”
mentioning
confidence: 99%
“… 4 Previous study 5 have examined the effects of magnesium on anesthetic agent doses needed to keep bispectral index (BIS) values within fixed ranges. However, only a single pediatric study 5 has evaluated the effect of intraoperative magnesium on BIS values while operation type and end-tidal anesthetic concentration were kept constant. This recent study had evaluated the depth of anesthesia only by intraoperative BIS values.…”
mentioning
confidence: 99%